Current Status of Mucoadhesive Gel Systems for Buccal Drug Delivery - Okur, Neslihan Ü.; Bülbül, Ece Ö.; Yağcılar, Ayşe P.; Siafaka, Panoraia I. (Current Pharmaceutical Design, 2021)
Background: Buccal drug delivery is a fascinating research field. Gel-based formulations present potent characteristics as buccal systems since they have great physicochemical properties. Methods: Among the various gels, in situ gels are viscous colloidal systems consisting of polymers; when physiological conditions change (pH, temperature, ion activation), they are transformed into the gel phase. These systems can improve bioavailability. Other systems, such as nanogels or emulgels can also be applied for buccal delivery with promising results. Polymeric gel-based systems can be produced by natural, semisynthetic, and synthetic polymers. Their main advantage is that the active molecules can be released in a sustained and controllable manner. Several gels based on chitosan are produced for the entrapment of drugs demonstrating efficient retention time and bioavailability due to chitosan mucoadhesion. Besides polysaccharides, poloxamers and carbopol are also used in buccal gels due to their high swelling ability and reversed thermal gelation behavior. Results: Herein, the authors focused on the current development of mucoadhesive gel systems used in buccal drug delivery. After explaining buccal drug delivery and mucoadhesion, various studies with hydrogels, in situ gels, and nanogels were analyzed as buccal gel systems. Various mucoadhesive gel studies with mucoadhesive polymers have been studied and summarized. This review is presented as valuable guidance to scientists in formulating buccal mucoadhesive drug delivery systems. Conclusion: This review aimed to assist researchers working on buccal drug delivery by summarizing buccal drug delivery, mucoadhesion, and buccal mucoadhesive gel systems recently found in the literature.
Keywords: Buccal drug delivery